THE EFFECTS OF LIQUID ORGANIC FERTILIZER VARIOUS AND Trichoderma Sp. ON THE GROWTH AND YIELD OF RED CABBAGE (Brassica oleraceae var. capitata forma rubra L.) - Ceria Dika Pertiwi; Heti Herastuti; Susilowati . (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2019)
Red cabbage is one of the vegetables that has a lot of nutrition content and it has a high economic value. This research aims to examine liquid organic fertilizer various and Trichoderma sp. on the growth and yeild of red gabbage (Brassica oleraceae var. capitata forma rubra L.). The research was conducted in May until July 2017 at Weron, Umbulharjo Village, Cangkringan, Sleman. This research used randomized complete block design (RCBD), 4 x 2 with four replications. The first factor was various of liquid organic fertilizer consists four variances: without liquid organic fertilizer, cow urine, bamboo root, and glereside. The second factor was Trichoderma sp. consists two variancese: without Trichoderma sp., and with Trichoderma sp. The observation result was analyzed by using Duncan Multiple Range Test (DMRT) at 5% level. The result showed that there were an interaction between liquid organic fertilizer various and Trichoderma sp. on the plant height at 42 days (the days after planting), the leaves number at 42 days (the days after planting), the root lenght, the roots number, and the crop weight of red cabbage. The treatment combination of cow urine and Trichoderma sp. gave the best crop weight compared to other treatments. There was no significant effect on vitamin C and vitamin A content in the red cabbage.Keyword: red cabbage, liquid organic fertilizer, Tricoderma sp.